PENINGKATAN EKONOMI DI MASA PANDEMI DI DESA PURO KECAMATAN KARANGMALANG KABUPATEN SRAGEN - Pramono Hadi; Amir Junaidi; Femi Sulaswaty; Ismiyanto Ismiyanto; Suparwi Suparwi; Suharno Suharno; Istiatin Istiatin; Priyono Priyono (LP2M STP Mataram, 2022)
Community service with the title Economic Improvement in the Pandemic Period in Puro Village, Karangmalang District, Sragen Regency. It has been held on Sunday, December 19, 2021. At the Puro village hall yard, starting at 10.00-11.30 WIB. The aim is to ease the economic burden of the Puro village community during the pandemic and the implementation of the tri dharma of higher education. The service method is carried out by initial surveys, implementation and evaluation of activities. The results of community service in Puro village, Karangmalang, Sragen district, have been carried out smoothly, successfully and have received support from stakeholders, both the security apparatus, namely the police, babinsa village apparatus and the Puro village community. The achievement of community service goals, namely; 1) Slightly ease the economic burden on the Puro village community in terms of basic needs, namely minimum basic necessities for the next few days; 2) It is carried out smoothly and successfully for the tri dharma activities of higher education, especially community service in 2021.